KAJIAN IMPLEMENTASI NORMA, STANDAR, PROSEDUR DAN KRITERIA DALAM PENGORGANISASIAN KAWASAN KESATUAN PENGELOLAAN HUTAN - Sylviani Sylviani; Elvida Yosefi Suryandari (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2013)
Forest Management Unit (FMU) is an area of forest land in site level that managed to meet sustainable forest management in along term plan. One or more forest functions (conservation, protection and production) can be included in an FMU, but the FMU will be classified by its dominant forest function. KPH has been established in several provinces, but a few them has not yet operational. Institutional aspects such as policy and organization are having problem in the implementation of FMU. The objective of the study are : (1) to analyze the implementation of norms, standards, procedures and criteria (NSPC) of FMU and (2 )to analyze the organization's policies in the management of FMU.The study was held at the Dampelas Tinombo FMU in Central Sulawesi; Way Terusan FMU, and Batu Tegi FMU in Lampung Province. In polic analysis used a retrospective method model, while in organizational structure analysis used qualitative descriptive method. The results showed that the policy about FMU NSPC has been implemented by each FMU in research location. It can be seen from the master plan of